Chapter 13 Masculine anxieties of undocumented South Asian male agricultural workers in Greece Productive use of bordering regimes and potential emasculation by racial capitalism - Kukreja, Reena (Taylor & Francis, 2023)
Foregrounding the ways in which men experience transnational migration, Migratory Men: Place, Transnationalism and Masculinities considers how we conceptualise and theorise mobile men in a global context. Bringing together studies from around the world (e.g. Australia, Pakistan, Tunisia, Zimbabwe and Italy), this collection foregrounds how the transnational migratory experience profoundly reshapes men's complex identity practices. Specifically, the collection highlights how transnational migratory aspirations and experiences often lead men to reimagine local patterns of masculinity and/or reaffirm prescriptive gender roles as they encounter new spaces/places. In presenting interdisciplinary research, the international scholars consider the powerful roles of economics, politics and social class in shaping masculinities. Furthermore, the contributors emphasise how men affectively and agentically experience migration and how interaction with new spaces/places can often lead to negotiations between disempowerment and empowerment. As such, this collection will appeal to both non-academic readers who share transnational migratory aspirations and experiences and academic readers across the social sciences with interests in gender and sexuality, migration and diaspora, transnationalism and contemporary masculinities.Chapters 13 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.